DINAMIKA PENGGUNAAN BAHASA GAUL DALAM INTERAKSI SOSIAL REMAJA DI ERA KOMUNIKASI MODERN - Yunita Shintauli Pasaribu; Mardiana Novitasari Togatorop; Yesa Alviona Br Torong; Nazwa Deril Aprilia; Sastra Veronika Sitohang (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of communication technology in the modern era has led to changes in adolescent social interaction patterns, one of which is through the use of slang in daily life (Desrina & Yelliza, 2025). Slang has become a part of adolescent communication styles used to create more relaxed, intimate social relationships that fit within their peer environment (Rosmaini et al., 2024). This study aims to analyze the dynamics of slang usage in adolescent social interaction in the modern communication era and to understand its impact on adolescent communication patterns. This research employs a literature review method with a qualitative descriptive approach through data collection from journals, scientific articles, and previous studies relevant to the research topic (Sugiyono, 2022).